2013
DOI: 10.1007/s00122-013-2090-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome sequence and identification of a candidate gene responsible for cytoplasmic male sterility in radish (Raphanus sativus L.) containing DCGMS cytoplasm

Abstract: A novel cytoplasmic male sterility (CMS) conferred by Dongbu cytoplasmic and genic male-sterility (DCGMS) cytoplasm and its restorer-of-fertility gene (Rfd1) was previously reported in radish (Raphanus sativus L.). Its inheritance of fertility restoration and profiles of mitochondrial DNA (mtDNA)-based molecular markers were reported to be different from those of Ogura CMS, the first reported CMS in radish. The complete mitochondrial genome sequence (239,186 bp; GenBank accession No. KC193578) of DCGMS mitotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 62 publications
6
41
1
1
Order By: Relevance
“…The inverted region has a pair of 442bp inverted repeats at its ends (100% identity between the inverted repeat sequences), which are the secondlargest pair of repeats in the genome (the largest repeat is 9,731 bp). Park et al (2013) reported that an Ogura-type CMS radish has multiple master-circle genome structures with a difference of a 79,976-bp inversion with a pair of 311-bp inverted repeats at the ends; however, this inversion is distinct from that reported here.…”
Section: Resultscontrasting
confidence: 71%
“…The inverted region has a pair of 442bp inverted repeats at its ends (100% identity between the inverted repeat sequences), which are the secondlargest pair of repeats in the genome (the largest repeat is 9,731 bp). Park et al (2013) reported that an Ogura-type CMS radish has multiple master-circle genome structures with a difference of a 79,976-bp inversion with a pair of 311-bp inverted repeats at the ends; however, this inversion is distinct from that reported here.…”
Section: Resultscontrasting
confidence: 71%
“…We also comparatively analyzed the mitochondrial genome of hau CMS with the mitochondrial genomes of nap [AP006444], cam [JF920285], jun [JF920288], ole [JF920286], car [JF920287], polima [FR715249] and ogura [AB694744] in Brassicas [1720]. A phylogenetic guide tree (Figure 7) and locally collinear blocks (Additional file 6) relating these eight sequenced mitochondrial genomes were calculated by using Neighbor Joining of the Mauve alignment system.…”
Section: Resultsmentioning
confidence: 99%
“…Since the first plant mitochondrial genome sequencing in Arabidopsis [3], a large number of mitochondrial genomes have been sequenced in angiosperm plants [410], especially in those that contain CMS cytoplasm. CMS-associated mitochondrial genome of crop species reported to date include Beta vulgaris [11], Oryza sativa [1214], Triticumae stivum [15], Zea mays [16], Brassica napus [17, 18], Raphanus sativus [19, 20]. In this study, the mitochondrial genome of hau CMS line, its maintainer line and the normal type line “J163-4” were fully sequenced and assembled into a master circle.…”
Section: Introductionmentioning
confidence: 99%
“…Novel and chimeric mitochondrial sequences are a frequent result of this recombination (Wise et al, 1987;Kennell and Pring, 1989;Wen and Chase, 1999;Gallagher et al, 2002;Okazaki et al, 2013;Yamagishi and Bhat, 2014;Tang et al, 2017), in which recombination sometimes leads to the creation of transcripts that interfere with normal male gametophyte development (Kitazaki and Kubo, 2010) via the generation of toxic and/or disruptive transmembrane proteins (Korth et al, 1991;Kim et al, 2007;Wan et al, 2007;Zhang et al, 2007;Yang et al, 2009;Gulyas et al, 2010;Jing et al, 2012;Flores-Renteria et al, 2013;Ji et al, 2013;Luo et al, 2013;Okazaki et al, 2013;Park et al, 2013;Hu et al, 2014). Surprisingly, such genes are not only abundant in many fertile plants, such as Arabidopsis thaliana Unseld et al, 1997), Beta vulgaris (Kubo et al, 2000), Oryza sativa (Notsu et al, 2002), Brassica napus (Handa, 2003), Zea mays (Clifton et al, 2004), Triticum aestivum (Ogihara et al, 2005), and Nicotiana tabacum (Sugiyama et al, 2005), but are also constitutively expressed.…”
Section: Discussionmentioning
confidence: 99%